Young Adults Undergoing CABG; A Multicenter Study - Fatima, Kisa; Ahmed, Sadaf; Mirza, Maria (Bangladesh Journal of Medical Science, 2024)
Objective: The aim of this study is to describe the population of young adults suffering from Coronary Artery Disease (CAD) and requiring coronary artery bypass grafting (CABG), and to assess early outcomes. And to identify risk factors in young patients undergoing CABG which is a major public health concern. Materials and Methods: This is a Cross-sectional study, designed as an observational/descriptive study, conducted with the non-probability method i.e. based on the subjective judgment of the researcher rather than the random selection. The study population will be recruited from five different hospitals of Karachi. These hospitals are selected with the consideration to the massive inflow of the patients. The Research tool that is going to be used in this study will account for participant’s previous data, personal and family history as provided by the patient at the time of procedure. The sample population of this study will be the patients who underwent elective CABG respectively. Patients aged 55 years or less undergoing CABG of both gender will be included. Result: Our study spots Mild to Severe stresses in subjects diagnosed with fatal Myocardial Infarction. Along with huge changes in other biochemical markers. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 808-811